Presence of human herpesvirus 6 variants A and B in saliva and peripheral blood mononuclear cells of healthy adults. - Aberle, S W (1996)
Saliva and peripheral blood mononuclear cells (PBMCs) from 44 healthy young adults were tested for human herpesvirus 6 variants A and B (HHV-6A and -6B) DNA by a sensitive nested PCR. HHV-6B infection was ascertained in 98% of the subjects, and 95% were found to excrete variant B in their saliva. HHV-6A was found in the PBMCs of 16%, but was not detected in saliva samples.